Literature Review: Study of Antibacterial Activity of Sunflower (Helianthus Annuus L.) Extract and Its Phytochemical Profiles - Rifka Amirul (Universitas Muhammadiyah Surakarta, 2020)
Sunflower is one type of plant that grows in Indonesia. Sunflower plants contain secondary metabolites that have antibacterial activity. This study was conducted using a literature review approach to determine the antibacterial activity of sunflowers. The steps taken in this literature review are to collect, identify, evaluate, and interpret the antibacterial activity of sunflowers. Search results from keywords “Sunflower”, “antibacterial”, and “phytochemical profile” obtained as many as 1,834 articles, from several articles search results were then reviewed and obtained 8 articles that matched the inclusion and exclusion criteria. Various antibacterial activities of sunflower are effective against Escherichia coli, Pseudomonas aeruginosa, Micrococcus luteus, Staphylococcus aureus, Bacillus subtilis, Propionibacterium acnes, Streptococcus uberis, and Aspergillus brasiliensis. The results of phytochemical screening of sunflower leaves revealed the presence of terpenoids, sesquiterpenoids, triterpenoids, and steroids. The bioactive components found in sunflower leaves include Heliannuol M, Heliannuol D, helivypolides K, helivypolides L, helieudesmanolide, tambulin, pinoresinol and sesquiterpene 10-oxo-isodauc-3-en-15-al. Factors that affect antibacterial activity include ozonation conditions, acidity value, and oil concentration. Overall it can be concluded that sunflower extract can inhibit bacterial growth.